2019
DOI: 10.1111/inm.12670
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in metabolic syndrome risk factors among patients with serious mental illness

Abstract: The prevalence of metabolic syndrome and its components continue to increase among patients with serious mental illness. This cross‐sectional study investigated whether metabolic syndrome prevalence and risk factors differ between male and female patients with serious mental illness. In total, 260 eligible patients were recruited from two hospitals. The data on demographic characteristics, lifestyle behaviour factors, biochemistry, and anthropometry were collected. Analyses were performed using multivariate lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
0
3
0
1
Order By: Relevance
“…Our study showed a significantly higher prevalence of hypertension, hyperlipidemia, abdominal obesity, and MetS in males than in females. However, some other studies have found that the prevalence of MetS was higher in females than in males [ 44 , 45 ]. The different results from different studies may be explained by the differences in hormones, lipid metabolism, population diversity, cultural behaviors, lifestyle habits, and the use of different diagnostic criteria.…”
Section: Discussionmentioning
confidence: 98%
“…Our study showed a significantly higher prevalence of hypertension, hyperlipidemia, abdominal obesity, and MetS in males than in females. However, some other studies have found that the prevalence of MetS was higher in females than in males [ 44 , 45 ]. The different results from different studies may be explained by the differences in hormones, lipid metabolism, population diversity, cultural behaviors, lifestyle habits, and the use of different diagnostic criteria.…”
Section: Discussionmentioning
confidence: 98%
“…As a result of constructing a multiple regression model, in which the value of the presence/absence of MetS acted as a dependent variable, there was a weak regression equation, that is, the studied predictors are weakly related to this variable. According to the results of other multivariate logistic regression analysis, the risk of developing MetS in people with mental disorders, is associated with different factors: in men, they include low educational level, high BMI, long duration of mental illness, concomitant chronic physical diseases and diagnosed bipolar disorder, while in women, aggravating factors include high BMI, marriage, and older age (52). The results obtained in our study indicate that the duration of schizophrenia, BMI, and the characteristics of antipsychotic therapy are not key factors in the development of MetS in patients with schizophrenia.…”
Section: Determinants Of Mets In Multiple Regression Analysismentioning
confidence: 99%
“…A comprehensive review of the literature from 1966 to 2010 revealed the likelihood of patients with SMIs developing Type 2 diabetes mellitus (T2DM) to be 2–3 times that of the general population (Ronne et al, 2020). Moreover, the prevalence of T2DM in patients with schizophrenia, bipolar disorder, and major depressive disorder are, respectively, 32.5%, 37.3%, and 30.5% (Tzeng et al, 2020). Taiwan's National Health Insurance Research Database has also revealed that, compared with the general population, patients with SMIs, especially those 60 years old or younger, develop T2DM more easily and receive medication for antihyperglycemia and antihyperlipidemia earlier in life (Bai et al, 2013; Chien et al, 2012; J. H. Hsu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%